The Accelerated Writing: Technology and Turbo-capitalism in the Twitterature by Santiago Eximeno (Ogigia. Revista Electrónica de Estudios Hispánicos, 2020)
The influence of the technology and the digital medium on Literature has brought about the development of some new writing forms inspired by a technographic concept of verbal art. Among the main examples of the productive relationship between word and technology, the Twitterature (minimal fiction reduced to 140 characters extension) must be pointed out, whose development is a result of the interaction and production by writers on Twitter. This is the case of the work Gas Mask (2012) by Santiago Eximeno (Madrid, 1973). This minimal fiction collection, firstly published on the well-known social media, can be regarded as a Twitterature paradigm in the context of the 21st-century Spanish literature. But the interest on the Eximeno’s work doesn’t lay exclusively on the way which an accelerated concept of the writing takes shape with Gas Mask. It’s also exemplary the critical vision of Eximeno’s micro-short fiction about the changes and dystopian spectres which have implied and might imply the technological innovation and the social transformation given by its implementation in the core of the turbo-capitalist economical system. Thus this paper focuses on reading Eximeno’s Twitterature in the light of the Literary theory argumentation about the narrative minimalism (Escandell, Gatica), as well as the main cultural and philosophical thought on accelerationism (Land, Jota-Pérez), the total screen simulacrum (Baudrillard, Žižek) or the burnout society (Han).
Keywords: Español; twitterature; literary minimalism; turbo-capitalism; accelerationism; the burnout society